2005
DOI: 10.1002/jcb.20490
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of regucalcin suppresses cell proliferation in cloned rat hepatoma H4‐II‐E cells: Involvement of intracellular signaling factors and cell cycle‐related genes

Abstract: The role of regucalcin, which is a regulatory protein in intracellular signaling pathway, in the regulation of cell proliferation was investigated by using the cloned rat hepatoma H4-II-E cells overexpressing regucalcin. The hepatoma cells (wild type) and stable regucalcin/pCXN2 transfectants were cultured for 72 h in a medium containing 10% fetal bovine serum (FBS) to obtain subconfluent monolayters. The proliferation of cells was significantly suppressed in transfectants cultured for 24-72 h. The proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 35 publications
6
101
0
Order By: Relevance
“…Over-expression of RGN in the rat hepatoma cell line H4-II-E was shown to suppress the expression of oncogenes c-myc, Haras, and c-src, and increase the expression of tumor suppressor genes p53 and Rb [23,24]. Recent studies in hepatoma cell lines also showed growth suppression effects by RGN [25,26]. Therefore, upregulation of RGN may provide the benefit of suppressing hepatocarcinogenesis in Sod1−/− mice, whereas reduced expression of RGN may have the opposite effect.…”
Section: Discussionmentioning
confidence: 98%
“…Over-expression of RGN in the rat hepatoma cell line H4-II-E was shown to suppress the expression of oncogenes c-myc, Haras, and c-src, and increase the expression of tumor suppressor genes p53 and Rb [23,24]. Recent studies in hepatoma cell lines also showed growth suppression effects by RGN [25,26]. Therefore, upregulation of RGN may provide the benefit of suppressing hepatocarcinogenesis in Sod1−/− mice, whereas reduced expression of RGN may have the opposite effect.…”
Section: Discussionmentioning
confidence: 98%
“…The breast cancer MDA-MB-231 cells (1x10 5 /ml per well) were cultured in a 24-well plate using DMEM containing 10% FBS and 1% P/S in the presence or absence of GV (1, 10, 50, 100 or 200 nM) for 1, 3, 7 or 14 days in a water-saturated atmosphere containing 5% CO 2 and 95% air at 37˚C (15)(16)(17). In separate experiments, the MDA-MB-231 cells (1x10 5 /ml per well) were cultured in DMEM containing 10% FBS and 1% P/S in the presence of either ethanol (0.1% final concentration; control), sodium butyrate (10 and 100 µM), roscovitine (10 and 100 nM), sulforaphane (1 and 10 nM), PD98059 (1 µM), staurosporin (0.1 µM), wortmannin (1 µM), DRB (1 µM) or gemcitabine (100 nM) for 3-7 days.…”
Section: Methodsmentioning
confidence: 99%
“…In separate experiments, the MDA-MB-231 cells (1x10 5 /ml per well) were cultured in DMEM containing 10% FBS and 1% P/S in the presence of either ethanol (0.1% final concentration; control), sodium butyrate (10 and 100 µM), roscovitine (10 and 100 nM), sulforaphane (1 and 10 nM), PD98059 (1 µM), staurosporin (0.1 µM), wortmannin (1 µM), DRB (1 µM) or gemcitabine (100 nM) for 3-7 days. Subsequent to the culture process, the cells were detached from each culture dish and counted (16,17). In addition, to determine the effects of GV on MDA-MB-231 cells that reached confluence, the cells (1x10 5 cells/ml per well) were cultured using a 24-well plate in DMEM containing 10% FBS and 1% P/S in the absence of GV for 7 days until they reached confluence, and then the cells were cultured in the presence of GV (1, 10, 50, 100 or 200 nM) for 3 days (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear regucalcin suppressed Ca Overexpression of regucalcin was found to play a role as a suppressor protein in cell proliferation that is mediated through various signaling stimulations in the cloned normal rat kidney proximal tubular epithelial NRK52E cells and the cloned rat hepatoma H4-II-E cells [31,34,35]. Regucalcin caused G1 and G2/M phase cell cycle arrest in these cells [31,36]. The anti-cell proliferation effect of regucalcin was not dependent on apoptosis; regucalcin suppresses apoptosis induced through multisignaling pathway [reviewed in Ref.…”
mentioning
confidence: 99%